Labour Welfare and Tax Benefits - Tongsamsi, Kanyaprin; Tongsamsi, Isara (Ph.D. in Social Sciences Journal, 2023)
This academic article aims to present both the legal form of workplace welfare and the support of welfare in the workplace outside of legal requirements, types of personal income tax, corporate income tax, and an examination of the relationship between labor welfare programs and the benefits of both personal and corporate income taxes. The business owner who has registered as a juristic entity is responsible for paying corporate income tax. While also having to pay personal income tax are those who work for the company or are considered workers. It compiles information from textbooks, academic literature, the Ministry of Labor’s report, laws, regulations, announcements, and Revenue Department directives, as an analytical framework. Findings are as follows: that annual company income tax is a requirement of labor welfare contracts. Employees who receive welfare benefits must be both required to be included and excluded as additional benefits or income when computing the annual personal income tax. These benefits are divided into 3 categories based on 3 tax benefits, namely: (1) The business establishment is deducted twice as tax expenses (2) The benefits received are not required to be included in the employee’s personal income, so the business is deducting taxes as they have actually been paid, and (3) Taxes that have already been paid are subtracted by the employer, and any benefits received by the employee must be reported as personal revenue. The above information will be useful to both entrepreneurs and employees for their annual tax planning.